Effect of Pleurotus Ostreatus on Pancreatic Beta Cells of Diabetes Mellitus Mice Model - Ningrum Wahyuni; Syafrudin Ilyas; Alya Amila Fitrie (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Over the last 30 years, the number of people suffering from diabetes mellitus has doubled globally. Adipose tissue dysfunction plays an important role in insulin resistance. Mushroom has been traditionally used to prevent diabetes. This research aims to study the anti-oxidative effect of Pleurotus ostreatus on pancreatic beta cells. This study is an experimental posttest only control group design. The subjects were 24 male wistar mice, divided into six groups. Group P0 was given distilled water and citrate buffer. Group P1 was given high fat diet (HFD) and low dose streptozotocin (STZ). Group P2 and 3 were given HFD and low dose STZ along with Pleurotus ostreatus ethanol extract. Group P4 and P5 were given HFD and low dose STZ, and then given Pleurotus ostreatus ethanol extract. Blood glucose levels and pancreatic beta cells area count were done after treatment. Data obtained was analyzed using one-way ANOVA test. One-way ANOVA test showed signifi cant difference in all the groups (p<0.05). Post Hoc test results showed difference in blood glucose levels and pancreatic beta cells area count. Pleurotus ostreatus ethanol extract can prevent cellular damage to murine pancreatic beta cells but unable to reverse the damage to the beta cells.